PENGARUH PENGGUNAAN PUPUK TERHADAP PERTUMBUHAN DAN HASIL PADI SAWAH - Misran Misran (UIR Press, 2014)
The use of fertilizers with the right amount could increase the growth and yield of lowland rice. This research aims to determine the effect of fertilizer use on the growth and yield of lowland rice. The experiment was conducted on the farmers field in Sungai Lareh, Koto Tangah District, Padang City of West Sumatera Province, from July to December 2009. Research used Randomized Completely Block Design (RCBD) with five replications. The treatments tested were: (A) Urea + KCl, (B) Urea + SP36, (C) Urea + SP36 + KCl, (D) without fertilizers (as control). The dosages of fertilizer were: 150 kg Urea, 100 kg SP36, and 75 kg KCl per hectare. The results showed that the use of a complete fertilizer (Urea + SP36 + KCl), or combination of Urea + KCl, or combination of Urea + SP36 had a significant effect on the growth and yield compared to without fertilizer treatment. The use of Urea + KCl resulted about 5.04 t/ha dry grains harvest (DGH) or increased grain yield as much as 14.03%, and the use of Urea + SP36 gave the results as much as 5.69 t/ha DGH or increased grain yields as much as 28.73%, and use of a complete fertilizer Urea + SP36 + KCl gave the results 6.13 t/ha DGH or increased yields about 38.69%. Whereas, without fertilized gave only grain yield as much as 4.42 t/ha DGH.